Students' Metacognition in Solving Numeracy Tasks Based on Adversity Quotient - Maulana, Hanief; Susiswo, Susiswo; Sudirman, Sudirman (PRISMA, 2024)
Metacognition is described as thinking about thinking and is often considered as a second-level cognition that is different from ordinary cognition. This study aims to describe the metacognition of students with adversity quotient (AQ) climber and camper types in solving numeracy tasks. The research used a qualitative-descriptive approach with the subjects of four students of class VIII MTs who were selected using purposive sampling technique based on the results of the Adversity Response Profile (ARP) test. Data were collected through numeracy tasks solving tests, task-based interviews, and observations, then analysed using thematic analysis involving data reduction, data presentation, and conclusion drawing. The results showed that AQ climber type students demonstrated metacognition consisting of metacognitive awareness, regulation, and evaluation with the steps of rethinking prior knowledge, planning the solution, and assessing the work. Meanwhile, AQ camper students showed metacognition in the form of metacognitive awareness, evaluation, and organisation with the steps of rethinking knowledge, evaluating abilities, redesigning plans, and evaluating completion steps. This study provides insight into the variation of metacognition based on AQ type, which can be used to design student character-based mathematics learning strategies.